CARA KERJA POLITIK UANG (Studi Kasus Pilkada dan Pilkades di Kabupaten Pati) - Fitriyah Fitriyah (Politika: Jurnal Ilmu Politik, 2015)
This study intends to explain the practices of money politics in local elections (Pilkada) and village head elections (Pilkades) in Pati regency using qualitative approach. Three people whose deep political knowledge and experience in both elections were purposively selected as informants. Data were collected by in depth interview and then qualitatively analyzed. The results showed that there were similarities of money politics in both Pilkada and Pilkades, including when the money was distributed and who were in charge as field operators, which were campaign staffs. A clientele relation was found inside the campaign staffs network. Money politics were abundant because of permissive votersKeywords: Pilkada, Pilkades, money politics